Regulatory Sandboxes for Novel Foods - Alexandra Molitorisová; Kai Purnhagen (European Journal of Risk Regulation)
This article conceptualises regulatory sandboxes in the food area, considering them as unique spaces with varying degrees of openness. Through an analysis of closed, semi-open and open spaces, it illustrates the regulatory landscape surrounding regulatory sandboxes of novel foods in the EU, particularly focusing on the concept of “placing on the market.” The article contends that the degree of openness of regulatory sandboxes impacts the application of the precautionary principle within these spaces. It explores scenarios where the sandbox tests various aspects of novel foods under EU soft and hard law. The characteristics of the regulatory sandbox (open, semi-open, closed) changes corresponding to what the regulatory sandbox tests in relation to a novel food, eg, a sensory characteristics or safety or other data points, such as effectiveness of labelling. This article contributes to the ongoing discourse on innovation-friendly laws surrounding regulatory frameworks applicable to novel foods in the EU.